"Racialized masculinities": A gendered response to marginalization among Malay boys in Singapore. Issue 1 (March 2019) - Ganapathy, Narayanan; Balachandran, Lavanya
While social disorganization and anomie theories are generally employed to explain the disproportionate representation of racial minorities in the offending population, such perspectives often fail to address the intersectionalities of class, race, religion, gender, and historicity that structurally marginalize the Malay youth in Singapore. This article hence adopts a neocolonial criminological approach in explaining racial disparity in crime, particularly how the Malay youth establish their dominance in gangs through hyper- and exaggerated forms of masculinity. Drawing on interviews with Singaporean Malay and Chinese individuals who were current and former gang members, this study shows that Malay youth tended to exhibit a blended masculinity comprising "Malayness" and "Chineseness" to compensate for their marginal status, highlighting their agentic capacity in strategically tapping upon an inventory of race resources to negotiate their gendered identities and attain status and economic mobility in the illegitimate society.